2009
DOI: 10.1111/j.1749-6632.2009.04774.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Linguistic Information Enhances Singing Proficiency in Occasional Singers

Abstract: In this study we examined the effect of reducing linguistic information on singing proficiency in occasional singers. Thirty-nine occasional singers were asked to sing from memory and to imitate three familiar melodies with lyrics and on the syllable /la/. Performances were analyzed with an acoustically based method yielding objective measures of pitch and temporal accuracy. Results obtained in production and imitation tasks revealed increased accuracy (e.g., fewer pitch interval errors and contour errors) whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 9 publications
5
39
2
Order By: Relevance
“…However, 2 singers did not improve; thereby, they were qualified as poor-pitch singers (similar cases of poor singing will be discussed below). We recently replicated these results (Berkowska & Dalla Bella, 2009; Dalla Bella & Berkowska, 2009) in a group of 39 occasional singers tested using different familiar material. In addition, we found that imitating a familiar song at a slow tempo enhanced both pitch accuracy and reduced temporal variability.…”
Section: Normal Singingmentioning
confidence: 53%
“…However, 2 singers did not improve; thereby, they were qualified as poor-pitch singers (similar cases of poor singing will be discussed below). We recently replicated these results (Berkowska & Dalla Bella, 2009; Dalla Bella & Berkowska, 2009) in a group of 39 occasional singers tested using different familiar material. In addition, we found that imitating a familiar song at a slow tempo enhanced both pitch accuracy and reduced temporal variability.…”
Section: Normal Singingmentioning
confidence: 53%
“…As the opposite dissociationimpaired beat perception with spared synchronization -has not been described so far, it is difficult to conclude whether there are two independent mechanisms involved. However, a functional separation of perception and action is not unusual, and is supported by a double dissociation in pitch processing (for reviews, see Dalla Bella, Berkowska, & Sowiński, 2011;Berkowska & Dalla Bella, 2009;. A similar functional architecture may apply to rhythm.…”
Section: Introductionmentioning
confidence: 99%
“…However, two participants did not improve, and were thereby qualified as 'poor-pitch singers' (see below for a discussion). The positive effect of reducing tempo on singing proficiency was confirmed more recently using a wider selection of melodies and a larger sample (Berkowska & Dalla Bella, 2009a;Dalla Bella & Berkowska, 2009).…”
Section: Singing Proficiency In the General Populationmentioning
confidence: 59%